Waste Reduction By Implementing Kaizen Activities In Textile Manufacturing Company - Tamby Suleiman, Nurusshahidah (2016)
Kaizen Activities (KA) is one of the Lean Manufacturing tools (LMT) usually being used to eliminate or reduce waste in manufacturing industries. KA is a continuous improvement method. This project was conducted to reduce waste by implementing KA in textile manufacturing industry. The company selected for this project is a textile manufacturing company located in Malacca. The company produces sewing and needlework products and one of the products is Pearliest Pin. This project was carried out in one of the process department of Pearliest Pin, head of pin dipping process. In head of pin dipping process of Pearliest Pin, there are four sub-processes involved and the first sub-process is mounting the pins on the boards using Carreone machine. There are two problems that occur in the pins mounting sub-process. The first problem is pin spillage problem, pins scattered around machine table and production floor during production. The second problem is bottleneck problem which involves the delay on action taken (by operator or supervisor) when processes have finished or when there are problems occurring. Based on the problems, three objectives have been generated for this project. The first objective of this project is to identify the problems that occur in the head of pin dipping process of Pearliest Pin. The second objective is to analyze the problems that occur in the head of pin dipping process of Pearliest Pin and the lastly, to propose solutions by implementing KA. The problems at head of pin dipping process of Pearliest pin were identified by the discussion with responsible personnel (workers involved in head of pin dipping process of Pearliest Pin), natural observational techniques, video recording and review of production history data. Then, to analyze the pin spillage problem, the data collected from natural observational techniques was converted into bar charts and Pareto Diagram. For the bottleneck problem, analysis on video recording and discussion with responsible personnel were done. Based on the analysis, the solutions for both problems were then generated by implementing KA. Pin spillage problem was solved in Mini Kaizen 1 and bottleneck problem was in Mini Kaizen 2. In Mini Kaizen 1, based on analysis of the problem, by creating new pins container the problem was solved. Three concept designs were generated and based on scoring method Design 2 was selected to be proposed for implementation. Prototype of Design 2 also has been tested in production line and shows that the total of pin spillage (waste) for Machine C reduced from 16.399g (before the implementation of prototype Design 2 based on observation and data collection in 2 hours) to 3.801g after the implementation of prototype of Design 2 (tested in2 hours). So, implementation of Design 2 is highly proposed to reducing pin spillage problem. In Mini Kaizen 2, based on analysis (brainstorming, and discussion), Andon board is proposed to be implemented in head of pin dipping process production line to reduce bottleneck problem. To fully eliminate pin spillage problem and bottleneck problem the KA should be performed continuously from time to time by the company.